SOSIALISASI PEMBELAJARAN YANG KREATIF DAN MENYENANGKAN MELALUI SULAP KIMIA KEPADA ANAK-ANAK SMA SE-KOTA MANADO - Akbar, Jakub Saddam; Rumengan, Stefan Marco; Maanari, Chaleb Paul; Djakariah, Djakariah (JUPADAI : Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract This community service program aims to introduce innovative approaches in learning chemistry to high school students in Manado City. The method used is to integrate the art of magic with basic chemistry concepts in an effort to increase students' interest and understanding of chemistry subjects. This program involves collaboration between chemistry teachers, students and the school community in Manado City. Student participation in this activity also increases collaboration between schools and universities in strengthening chemistry education at the local level. Findings from this program provide insights for more inclusive and engaging learning approaches in the future. It is hoped that the results of this program can become the basis for developing more innovative learning strategies in increasing students' interest in chemistry.